Oxide ceramic fibers via dry spinning process—From lab to fab - Scholz, Hermann; Vetter, Johannes; Herborn, Ralf; Ruedinger, Arne (International Journal of Applied Ceramic Technology, 2020)
Oxide fibers preparation and manufacturing capabilities at Fraunhofer-Center HTL are introduced, showing the development and preparation of oxide ceramic fibers from lab scale to pilot scale up to near production scale. As a specific example, the development of an aluminosilicate fiber with mullite composition is discussed in more detail. Fiber development started from nonaqueous sol-gel precursors in the early lab scale. With increasing fiber spinning volume, precursors were switched to water-soluble systems. Transformation from green fiber to ceramic fiber was monitored by thermogravimetric and differential thermal analysis, X-ray diffraction, and scanning electron microscopy. The evolution of ceramic phases, microstructure formation, and the effects on tensile strength and Young's modulus were investigated. Weibull statistics and fracture analysis helped to understand the results. Next step will be the transition from large lab scale to pilot scale, demonstrating manufacturing capability.
Created from Fastlane, Scopus look-up